The new rules of lifting supercharged : ten all-new muscle-building programs for men and women - Schuler, Lou (Avery, a MEMBER Of PENGUIN GROUP (USA) INC., 2012)
"A revised edition of the first The New Rules of Lifting, which will appeal to both novices as well readers who loved the original but are ready for version 2.0"--